1999
DOI: 10.1038/sj.onc.1202329
|View full text |Cite
|
Sign up to set email alerts
|

Linkage between melanocytic tumor development and early burst of Ret protein expression for tolerance induction in metallothionein-I/ret transgenic mouse lines

Abstract: We examined the basis of the all or none dierence in inducing melanocytic tumor development among three transgenic mouse lines (304, 192 and 242) to which the same promoter-enhancer (metallothionein-I) and oncogene (ret) were introduced. We initially demonstrated that both skin melanosis and Ret protein expression in skin, thymus and brain ®rst became detectable before or immediately after birth in the mice of the tumor developing lines (304 and 192), whereas they became detectable a few days after birth in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 15 publications
2
38
0
Order By: Relevance
“…Based on the results obtained, we would propose that UV also affects proteins as oncogene products for superactivation, which might be involved in the mechanism of stepwise oncogenesis. Partially supporting this view, we have observed that repeated UV irradiation of otherwise benign melanocytic tumors developed in RETtransgenic mice (Iwamoto et al, 1991;Kato et al, 1999) induced their malignant transformation, accompanying extensive superactivation of Ret (our unpublished results), although the exact cause-and-effect relation of these two events remains to be proved.…”
Section: Discussionmentioning
confidence: 54%
“…Based on the results obtained, we would propose that UV also affects proteins as oncogene products for superactivation, which might be involved in the mechanism of stepwise oncogenesis. Partially supporting this view, we have observed that repeated UV irradiation of otherwise benign melanocytic tumors developed in RETtransgenic mice (Iwamoto et al, 1991;Kato et al, 1999) induced their malignant transformation, accompanying extensive superactivation of Ret (our unpublished results), although the exact cause-and-effect relation of these two events remains to be proved.…”
Section: Discussionmentioning
confidence: 54%
“…Due to the transport of MT out of the cells, its level is significantly reduced in intracellular space. With respect to the MT relation to zinc ions, whose metabolism is abnormal in the prostate tumor tissue, MT participation on pathogenesis of malignant disorder can be expected [45][46][47][48][49][50][51][52][53]. To date, there is no evidence in the literature determining metallothionein level in 22Rv1 and PNT1A cell lines, however, there were done some experiments describing behaviour of RWPE-1 cell line, which revealed similarities of behaviour of this cell line with prostate tissue [54] as well as in the case of PC-3 cell line [55].…”
Section: Discussionmentioning
confidence: 99%
“…After the membranes had been reacted with the anti-Ret (reactive to both c-Ret and RFP-RET; Immuno-Biological laboratories, Gunma, Japan) antibody, the reaction was examined using Western Blot Chemiluminescence Reagent (DuPont NEN, Boston, MA, USA). Immunoprecipitation and immunohistochemistry with antiRet antibody (Kato et al, 1999(Kato et al, , 2000 or anti-S-100 protein (Iwamoto et al, 1991) were performed as described previously.…”
Section: Immunoblot Immunoprecipitation and Immunohistochemistrymentioning
confidence: 99%
“…Previously, we established four transgenic mouse lines (line 192, line 242, line 304 and line 319) by introducing the RFP-RET oncogene, fused to the mouse metallothionein-l promoter-enhancer (Iwamoto et al, 1991;Kato et al, 1998bKato et al, , 1999 for a broad spectrum of expression, which encodes an activated form of RET kinase. The genetic background of the original RFP-RET-transgenic mice was F1 of C57BL/6 and BALB/c strains (Iwamoto et al, 1991).…”
Section: Preparation Of Micementioning
confidence: 99%
See 1 more Smart Citation